2012
DOI: 10.1111/j.1533-8525.2012.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of World Societal Forces on Social Tolerance. A Time Comparative Study of Prejudices in 32 Countries

Abstract: Societal variation in xenophobia, homophobia, and other prejudices is frequently explained by the economic background and political history of different countries. This article expands these explanations by considering the influence of world societal factors on individual attitudes. The empirical analysis is based on survey data collected within the World Value Survey and European Values Study framework between 1989 and 2010. Data are combined to a three‐wave cross‐sectional design including about 130,000 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 49 publications
1
58
0
7
Order By: Relevance
“…Given the rise in support for right-wing political parties across Britain and mainland Europe during the last decade, a pertinent education effect for our analyses is the association between lower levels of education and greater ingroup favoritism (Jackman & Muha, 1984;Stouffer, 1955). A range of studies analyzing data collected in Europe have found that lower education levels are associated with greater levels of prejudice, ethnic exclusionism, xenophobia, and negative attitudes towards immigration and immigrants (Hainmueller & Hiscox, 2007;Hello, Scheepers, & Gijsberts, 2002;Jenssen & Engesbak, 1994;Pettigrew et al, 1997), whereas studies in the US and using international data have found that lower levels of education are associated with nationalism (Coenders & Scheepers, 2003;Coenders, 2001), prejudice (Hadler, 2012;Kuppens & Spears, 2014), and immigration attitudes (Maria, 2004).…”
Section: Four Varieties Of Education Effectmentioning
confidence: 99%
“…Given the rise in support for right-wing political parties across Britain and mainland Europe during the last decade, a pertinent education effect for our analyses is the association between lower levels of education and greater ingroup favoritism (Jackman & Muha, 1984;Stouffer, 1955). A range of studies analyzing data collected in Europe have found that lower education levels are associated with greater levels of prejudice, ethnic exclusionism, xenophobia, and negative attitudes towards immigration and immigrants (Hainmueller & Hiscox, 2007;Hello, Scheepers, & Gijsberts, 2002;Jenssen & Engesbak, 1994;Pettigrew et al, 1997), whereas studies in the US and using international data have found that lower levels of education are associated with nationalism (Coenders & Scheepers, 2003;Coenders, 2001), prejudice (Hadler, 2012;Kuppens & Spears, 2014), and immigration attitudes (Maria, 2004).…”
Section: Four Varieties Of Education Effectmentioning
confidence: 99%
“…Likewise, we find differences in terms of sex, girls being less xenophobic in general, and the greater the cultural diversity, the lower the levels of xenophobia. In other words, ethnic and gender diversity reduce the amount of xenophobia (Hadler 2012;Hjerm 2005). In turn, it has been observed that the effect of education is increased when it is complemented by help from international organisations whose work reinforces and aids understanding of teachers' discourse (Hadler 2012).…”
Section: Teachers' Discourses and Expectationsmentioning
confidence: 99%
“…In other words, ethnic and gender diversity reduce the amount of xenophobia (Hadler 2012;Hjerm 2005). In turn, it has been observed that the effect of education is increased when it is complemented by help from international organisations whose work reinforces and aids understanding of teachers' discourse (Hadler 2012). Countries with high levels of xenophobia would include India, France and Turkey, among many others.…”
Section: Teachers' Discourses and Expectationsmentioning
confidence: 99%
“…Mivel Magyarországon korábban nem készült hasonló kutatás a témában, így elsősorban azokra a magyar kutatási eredményekre támaszkodhatunk előzményként, amelyek a homofóbiával kapcsolatos attitűdök vizsgálatára koncentráltak (Takács-Szalma 2011, 2012.…”
Section: Az Azonos Nemű Párok öRökbefogadásával Kapcsolatos Attitűdökunclassified
“…Ezzel az eredménnyel -ahogy ezt a 2. ábra is mutatja -Magyarország a kevésbé toleráns európai társadalmak közé sorolható (Takács 2011;Takács-Szalma 2011;2012).…”
Section: Itt a "Hagyni Kell Hogy A Meleg Férfiak éS A Leszbikus Nőkunclassified